SAT0523 Evolution of visual affection in patients with giant cell arteritis treated with tocilizumab. (12th June 2018) - Prieto-Peña, D.; Loricera, J.; Moriano, C.; Díez, E.; Nárvaez, J.; Mera, A.; Pérez-Pampín, E.; Aldasoro, V.; Varela, M.; Álvarez-Rivas, N.; Barbazán, C.; Ordás-Calvo, C.; et al.
Abstract : Background: Giant cell arteritis (GCA) is a large vessel vasculitis that has a special predilection for extracranial branches of the external carotid artery. Among its most fearsome complications is visual affectation. Tocilizumab (TCZ) is a monoclonal antibody directed against the interleukin 6 receptor that has shown utility in the treatment of GCA. Objectives: Our aim was to assess the evolution of visual clinic in patients with GCA treated TCZ. Methods: Retrospective multicentre study of 20 GCA patients with visual involvement treated with TCZ. The efficacy of this drug on visual symptoms was evaluated. Results: We evaluated 20 patients (14 women and 6 men) with a mean age ±SD of 73.7±10.1 years with GCA and visual symptoms. In total there were 23 affected eyes. The symptoms reported were: unilateral blindness (n=6), unilateral blurred vision (n=6), unilateral amaurosis fugax (n=3), unilateral hemianopsia (n=2), bilateral blindness (n=1), bilateral blurred vision (n=1), bilateral hemianopsia (n=1). Before starting treatment with TCZ all patients had received high doses of prednisone, with a mean ±SD of 54.2±13.8 mg/day (range of doses: 40–80 mg/day). In addition, 9 of them also received intravenous corticosteroid boluses. In addition, 13 patients received traditional immunosuppressants: methotrexate (MTX) (n=12), cyclophosphamide (n=2), leflunomide (n=1) and azathioprine (n=1). Regardless of corticosteroids, TCZ was administered as monotherapy in 14 patients, while in 6 it was administered in combination with MTX. The TABLE shows the evolution of the visual affectation of these patients. Throughout a median follow-up [RIC] of 9 4–18 months, none of the 7 patients who had a blindness regained vision. The 2 patients who presented unilateral hemianopsia recovered vision. The patient with bilateral hemianopsia and the patient with bilateral blurred vision experienced a partial improvement. The rest of the patients achieved a complete recovery. Conclusions: Although TCZ seems to be also useful in the treatment of visual manifestations of ACG, once blindness is established, it does not seem to be effective. Disclosure of Interest: None declared